2013
DOI: 10.1007/s10072-013-1435-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing GABAergic cell populations in the thalamic reticular nucleus of normal and genetic absence epilepsy rats from Strasbourg (GAERS)

Abstract: The GABAergic neurons of the thalamic reticular nucleus (TRN) play a critical role in the generation and control of spike-and-wave discharges (SWDs) in absence epilepsy. We have used the disector method to count the GABA+ve and GABA-ve neurons in the intermediate TRN sector of genetic absence epilepsy rats from Strasbourg (GAERS) and of Wistar rats during postnatal (P) development at P10, P20, P30, and P60 days. The same part of TRN was removed from each animal, the GABAergic neurons were labelled using light-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…A developmental increase in the number of the GABA-IR neurons in GAERS and NEC, but not in the Wistar, NRT was observed in this study from P15 to P25-P90. Other authors have shown a similar increase at P10 to P20 in both Wistar and GAERS but a progressive decrease at P60 only in GAERS ( Cavdar et al., 2013 ), while a reduction in Wistar at both P90 and P720 in Wistar ( Ramos et al., 1995 ). As it does occur in both GAERS and NEC, it is unlikely that the increased density of NRT GABA-IR neurons in GAERS during development is related to the expression of the absence phenotype.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…A developmental increase in the number of the GABA-IR neurons in GAERS and NEC, but not in the Wistar, NRT was observed in this study from P15 to P25-P90. Other authors have shown a similar increase at P10 to P20 in both Wistar and GAERS but a progressive decrease at P60 only in GAERS ( Cavdar et al., 2013 ), while a reduction in Wistar at both P90 and P720 in Wistar ( Ramos et al., 1995 ). As it does occur in both GAERS and NEC, it is unlikely that the increased density of NRT GABA-IR neurons in GAERS during development is related to the expression of the absence phenotype.…”
Section: Discussionmentioning
confidence: 58%
“…Three methodological issues should be considered before discussing the differences between our findings and those of previous studies in GAERS. First, we used a GABA monoclonal antibody whereas previous investigations in GAERS have employed polyclonal antibodies ( Cavdar et al., 2013 , Cavdar et al., 2014 , Cavdar et al., 2012 ). Second, different GAERS colonies, though all derived from the original strain in Strasbourg ( Depaulis et al., 2016 , Vergnes et al., 1987 ), show diverse AS phenotypes, potentially resulting from different lengths of inbreeding and environmental conditions at diverse establishments ( Powell et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the VPL nucleus because it receives information from the hindlimb (Joseph T Francis et al, 2008) and relays it to the somatosensory cortex; the corresponding cortical microcircuit was reconstructed in a previous model (Markram et al, 2015a). The Rt is intimately associated with the different thalamic nuclei and it is the primary source of inhibition to the thalamus (Cavdar et al, 2013; de Biasi et al, 1986; Houser et al, 1980; Pinault, 2004). Since the VPL does not have a clear modular organization, we followed a previously published approach to define the microcircuit radius and its height (Markram et al, 2015a).…”
Section: Resultsmentioning
confidence: 99%
“…Aside from the widely different proportions that have been reported in section 4.3, almost nothing is known about their electrophysiological properties, their connectivity, their morphologies, and their functional role. Also puzzling is the report of non-GABAergic neurons in Rt (Cavdar et al, 2013). Further, only a few paired-recording studies have investigated the inhibition between interneurons and TC cells comprehensively, with none reporting on the short-term plasticity dynamics of IPSP at the interneuron-TC synapse.…”
Section: Outstanding Knowledge Gapsmentioning
confidence: 99%